Avaliação funcional e de habilidades sociais de adolescentes com paralisia cerebral - Silva, Letícia Thays Bessa (2021)
The demands on socio-cultural aspects are greater for adolescents with cerebral palsy, mainly due to the conditions that are imposed on the team itself. When analyzing the importance of Social Skills in the development of behaviors that can contribute to the development of the repertoire that the present study has as a general objective: to evaluate the Functional and Social Skills repertoire of adolescents with cerebral palsy. As specific objectives: to identify the levels of gross motor function and communication; description of the social skills most present in the repertoire of adolescents with cerebral palsy; in recognizing which classes of social skills have behavioral deficits; and relate the variables Social Skills, motor, communicative characteristics, economic classification and type of school among adolescents with cerebral palsy. This is an observational analytical study. The sample is non-probabilistic for convenience. Access to participants occurs by referral from the contact of the researcher with professionals, associations and institutes, and was initiated after approval by the Ethics Committee on Research with Human Beings at the Federal University of São Carlos. Still as a preliminary step a pilot study was carried out with the participation of two twin adolescents with cerebral palsy and the mother-mother. The study sample included 15 adolescents with cerebral palsy, five adolescents with articulate speech and ten without articulated speech, and the main caregivers. The instruments used were: (a) Participant Identification Form; (b) Brazil's Economic Classification Criterion. (c) Expanded and revised gross motor function classification system; (d) Communication Function Classification System; (e) Pediatric Disability Assessment Inventory - Adaptive Computerized Testing - adapted Brazilian version; (f) Inventory of Social Skills for Students Without Articulated Speech; and (g) Adolescent Social Skills Inventory. Data analysis takes place based on the rules for interpreting the manual for each instrument. The results indicated that there is no decrease in the total score of Social Skills among groups of adolescents with articulate speech and without articulated speech, however all adolescents have deficits in the development of these skills. The group of adolescents without articulate speech is motorized and communicatively more committed, their resources also present greater losses and are predominantly schooled in special schools. However, no relationship was found between these characteristics and the Social Skills of the entire sample. There was instrumental difficulty in characterizing the repertoire of Social Skills in the application of the instruments with those participants without articulated speech and who do not have an alternative effective communication system, therefore, the development and / or adaptation of instruments in this population is indicated, and that is capable to identify the different types of deficits. In addition, it emphasizes the need for greater access by this population to alternative resources and systems that favor their independence, and the importance of school for this population and the development of social skills. The results indicate the need for intervention programs in Social Skills to be carried out with this population, as well as studies that contemplate other areas of knowledge in the interface of psychology and special education with cerebral palsy and adolescence for the advancement of the area.